2022
DOI: 10.1186/s12888-022-04416-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum homocysteine in first episode and drug-naïve individuals with schizophrenia: sex differences and correlations with clinical symptoms

Abstract: Background Accumulating evidence shows that homocysteine (Hcy) is implicated in the pathophysiology of schizophrenia, and plays an important role in clinical characteristics. This study evaluated the relationships between Hcy levels and clinical features in first-episode, Chinese Han, drug-naïve (FEDN) patients with schizophrenia. Methods FEDN individuals (119 with schizophrenia and 81 healthy controls matched for age, sex, education, and body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
2
4
0
Order By: Relevance
“…One explanation could be for this finding in terms of the clinical severity of SZ. Prior studies showed positive correlations between plasma Hcy levels and PANSS scores 11 13 , and we also confirmed a significant positive correlation of plasma Hcy levels with PANSS-total score and PANSS-general psychopathology subscale score. These findings suggest that a population with SZ of lower clinical severity may exhibit lower plasma Hcy levels.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One explanation could be for this finding in terms of the clinical severity of SZ. Prior studies showed positive correlations between plasma Hcy levels and PANSS scores 11 13 , and we also confirmed a significant positive correlation of plasma Hcy levels with PANSS-total score and PANSS-general psychopathology subscale score. These findings suggest that a population with SZ of lower clinical severity may exhibit lower plasma Hcy levels.…”
Section: Discussionsupporting
confidence: 88%
“…A Mendelian randomization analysis yielded an odds ratio of 2.15 per 1-SD increase in plasma Hcy levels 10 . Additionally, several studies, including one conducted in drug-naïve, first-episode psychosis patients 11 , have reported that plasma Hcy levels are positively correlated with the clinical severity of SZ using the Positive and Negative Syndrome Scale (PANSS) 11 13 . Therefore, these findings implicate increased Hcy as a part of the biological etiology of SZ.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Hcy levels can be effectively reduced by B vitamin and folic acid supplementation, which may be beneficial for reducing SP-associated negative symptoms 23 . Zhilyaeva et al have observed that PANSS negative symptom scores, including difficulty with abstract thinking, lack of spontaneity and fluency in conversation, stereotyped thinking, and motor retardation, were more pronounced in SP patients with elevated Hcy levels, supporting the positive association between PANSS and high Hcy levels that we observed 24,25 . It has been also evaluated that patients with SP perform worse on cognitive assessments, and high levels of Hcy are associated with this 26–28 …”
Section: Discussionsupporting
confidence: 84%
“…23 Zhilyaeva et al have observed that PANSS negative symptom scores, including difficulty with abstract thinking, lack of spontaneity and fluency in conversation, stereotyped thinking, and motor retardation, were more pronounced in SP patients with elevated Hcy levels, supporting the positive association between PANSS and high Hcy levels that we observed. 24,25 It has been also evaluated that patients with SP perform worse on cognitive assessments, and high levels of Hcy are associated with this. [26][27][28] Some articles have shown an association between elevated Hcy levels and cognitive dysfunction in patients with SP.…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine is a component of one-carbon metabolism, which is involved in synthesizing methyl donors and the antioxidant glutathione (GSH). Thus, abnormalities in homocysteine may disturb normal methylation reactions, including DNA methylation, detoxification of xenobiotics via GSH conjugation, and redox regulation by GSH antioxidant activity [ 13 ]. In addition to the dysregulation of these signaling factors, cerebral volume is consistently reported to be lower in patients with schizophrenia [ 14 , 15 ], partly due to a reduction in myelin volume [ 16 ].…”
Section: Introductionmentioning
confidence: 99%